Commentary: How to have agency in a pandemic - Jones, Rodney H. (Frontiers in Artificial Intelligence, 2024)
This commentary reflects on the collection of articles in the Research Topic "Unhealthy Language," focusing on what they can teach us about the relationship between language and agency in times of crisis. It interrogates they way agency is addressed by the different contributors through three different frameworks: a linguistic framework that focuses on how agency is encoded in and enacted through language, a framework based on practice theory that focuses on how agency emerges through social interactions, and a framework informed by posthuman and new materialist perspectives that sees agency as performed within networks of human and non-human actors. It ends by arguing that, while all of these perspectives provide insights into how language shapes agency, they do not provide an adequate roadmap for how to understand and enact agency in a global crisis such as a pandemic. For this, it is argued, a new perspective on agency is needed, one which focuses more on collective action, generosity, and learning to respond to others.The main contribution of this commentary article is that it provides a reflective synthesis of the diverse perspectives on the relationship between language and agency in applied and sociolinguistics and examines the consequences of these different perspectives for understanding how people interact and communicate during times of crisis. In doing so, the commentary highlights important insights from each perspective, but also critiques their limitations in fully making sense of the complex negotiations of agency that occurred during the pandemic, and calls for new approaches to language and agency that focus as much on listening as on speaking and seek to reveal how language can help to create the conditions for collective action and empathy.